Recent advances in the roles of exosomal microRNAs in neuroblastoma - Bhavsar, Swapnil Parashram (Frontiers in Oncology, 2023)
Exosomal miRNAs (exo-miRs), universally found in biofluids, tissues, and/or conditioned medium of the cell cultures play a significant role in cell - cell communication, thus driving cancer progression and metastasis. Very few studies have explored the role of exo-miRs in the progression of children’s cancer - neuroblastoma. In this mini review, we briefly summarize the existing literature on the role of exo-miRs in the pathogenesis of neuroblastoma.